Intradermal Testing With COVID-19 mRNA Vaccines Predicts Tolerance - Stehlin, Florian; Mahdi-Aljedani, Rima; Canton, Loris; Monzambani-Banderet, Véronique; Miauton, Alix; Girard, Cedric; Kammermann, Kevin; Meylan, Sylvain; Ribi, Camillo; Harr, Thomas; Yerly, Daniel; Muller, Yannick D. (Frontiers in Allergy, 2022)
Background The newly developed mRNA-based COVID-19 vaccines can provoke anaphylaxis, possibly induced by polyethylene glycol (PEG) contained in the vaccine. The management of persons with a history of PEG allergy or with a suspected allergic reaction after the first dose remains to be defined. Methods In this real-life study, we defined two cohorts of individuals: one pre-vaccination including 187 individuals with high-risk profiles for developing anaphylaxis and a second post-vaccination including 87 individuals with suspected allergic reactions after the COVID-19 mRNA vaccine. Upon negative skin test with an mRNA vaccine, a two-step (10–90%) vaccination protocol was performed. Positive skin tests were confirmed with the basophil activation test (BAT). Results Among 604,267 doses of vaccine, 87 suspected allergic reactions (5 after the booster) were reported to our division for further investigations: 18/87 (21%) were consistent with anaphylaxis, 78/87 (90%) were female, and 47/87 (54%) received the BNT162b2 mRNA vaccine. Vaccine skin tests were negative in 96% and 76% of the pre- and post-vaccination cohorts, respectively. A two-step vaccination was tolerated in 232/236 (98%) of individuals with negative tests. Four individuals experienced isolated asthmatic reactions during the two-step challenge. Vaccine-positive skin tests were consistently confirmed by BAT; CD63 and CD203c expression was selectively inhibited with ibrutinib, suggesting an IgE-dependent mechanism. Conclusion Sensitization to SARS-CoV-2 mRNA vaccines can be detected with intradermal testing. Significantly more individuals were sensitized to mRNA vaccines in the post-vaccination cohort. A two-step 10–90%-vaccination protocol can be safely administered upon negative skin testing.